HUBUNGAN SELF-COMPASSION DENGAN BURNOUT PADA IBU RUMAH TANGGA - Nadine, Nadine Febrina; Sahrani, Riana (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2025)
A housewife plays a central role in the family, facing endless housework and various demands in caring for children and the family. The consistent juggling of work and family management subject’s mothers to mental and psychological fatique, leading to burnout a condistion of excessive mental pressure resulting in fatique. One potential solution to overcome burnout is self-compassion, defined as a feeling of acceptance and openness to the misery or mistakes one experiences. It involves not distancing oneself but rather fortering a desire to alleviate suffering and restore oneself with generosity. Applying self-compassion can empower indivduals in time of fragility and imperfection. This research aims to explore the relationship between self-compassion and burnout in housewives, utilizing a quantitative correlation methodology. The Burnout Scale and the Self-Compassion Scale (SCS) serve as measurement tools. Among the 388 participants, low levels of burnout were reported, with 341 experiencing high levels of self-compassion. The correlation result between self-compassion and burnout variables revealed a significant negative correlation, with values of r = 1,000 and p = 0,000 (p<0,05). This study demonstrates that a higher level of self-compassion in housewives is associated with lower burnout, and conversely, higher burnout is link to lower self-compassion.